INNV-29. PROFESSIONAL PRACTICE MODEL FOR ADVANCED PRACTITIONERS IN NEURO ONCOLOGY - Cone, Christina (Neuro Oncol, 2020)
BACKGROUND: Neuro-oncology advanced practitioners (APs - nurse practitioners, physician assistants) require specialization beyond the scope of population-based generalist training and education. There are no specialty standards or certifications for neuro-oncology APs, no formal training programs, and no literature that addresses the competency requirements of neuro-oncology APs. The burden of AP turnover at an academic medical center ambulatory neuro-oncology practice was as high as 50%. This quality improvement project’s purpose was to develop a professional practice model (PPM) to support the professional development and retention of APs. METHODS: Using the Focus, Analyze, Develop, Execute and Evaluate (FADE) quality improvement methodology the authors (1) reviewed literature and relevant professional organizations to identify possible professional competencies for neuro-oncology APs, (2) analyzed data to develop evidenced-based practice domains, (3) used purposive sampling to recruit a team of neuro-oncology experts, (4) conducted a Delphi study with the experts to gain consensus on practice domains and professional competencies, and finally (5) utilized the Delphi study results to create a PPM for neuro-oncology APs. RESULTS: The authors recruited twenty-three participants (39% were physicians, 57% were APs, and 4% were administrators) for the Delphi study, which was executed via electronic transmission using Qualtrics. Participants reached consensus on six domains of practice (Medical Knowledge, Interprofessional Collaboration/Communication, System-based Practice, Professionalism, Practice-based learning, Patient/family-centered care) and fifty corresponding competency statements after two rounds of the Delphi. With the implementation of the PPM and the development of standardized onboarding, the AP turnover rate decreased from 50% to 12% in just two years. CONCLUSION: This QI project successfully created a PPM for a neuro-oncology AP team. The PPM supports neuro-oncology APs by validating their unique skill set that combines several specialties. The PPM provided the framework to standardize orientation/training, evaluate performance, and promote job satisfaction and retention.